KONSEP SAKINAH, MAWADDAH DAN RAHMAH DALAM AL-QUR’AN (PRESPEKTIF PENAFSIRAN KITAB AL-QUR’AN DAN TAFSIRNYA) (UINSI Samarinda, 2015)
One of the purposes of marriage is to create a sakinah (tranquil), mawaddah (affectionate) and rahmah (merciful) life among a husband, a wife and their children. The sakinah, mawaddah and rahmah’s life, however, does not come in handy with the marriage. It must be striven by both men and wives during their marriage. What does the Qur’an say about the concept of sakinah, mawaddah, and rahmah? This article elaborates on these concepts as enshrined in al-Rum : 21 as per the interpretation and translation of the Ministry of Religious Affairs. The Ministry’s interpretation and translation of the verse is necessary to be analysed given its wide use by Muslims in Indonesia. This article finds that the Ministry’s interpretation is not much different from the interpretation put forward by other Qur’anic commentators; it even makes reference to various opinions of the scholars.